2015
DOI: 10.1249/mss.0000000000000690
|View full text |Cite
|
Sign up to set email alerts
|

Oxandrolone Augmentation of Resistance Training in Older Women

Abstract: Oxandrolone improves body composition adaptations to PRT in older women over 12 wk without augmenting muscle function or functional performance beyond that of PRT alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…This was considerable higher than the effect of the present study (LBM changes: WB-EMS 0.72 kg, WB-EMS&P 0.63 kg); however, in the older study fraction of this meta-analysis, the gains were much lower than the average. In an extreme case of combining high intensity resistance exercise for 12 weeks with anabolic steroids (oxandrolone), Mavros et al [43] observed a 2.6 kg (95 % CI 1.0-4.2 kg) gain in LBM in pre-frail older women (75 ± 7 year). Furthermore, body fat decreased significantly in this oxandrolone group (1.0 kg; 0.4 to 1.6 kg), while the placebo-controlled resistance exercise group of Mavros [43] gained fat mass (0.5 kg) and showed only slight increments of LBM (0.4 kg).…”
Section: Discussionmentioning
confidence: 99%
“…This was considerable higher than the effect of the present study (LBM changes: WB-EMS 0.72 kg, WB-EMS&P 0.63 kg); however, in the older study fraction of this meta-analysis, the gains were much lower than the average. In an extreme case of combining high intensity resistance exercise for 12 weeks with anabolic steroids (oxandrolone), Mavros et al [43] observed a 2.6 kg (95 % CI 1.0-4.2 kg) gain in LBM in pre-frail older women (75 ± 7 year). Furthermore, body fat decreased significantly in this oxandrolone group (1.0 kg; 0.4 to 1.6 kg), while the placebo-controlled resistance exercise group of Mavros [43] gained fat mass (0.5 kg) and showed only slight increments of LBM (0.4 kg).…”
Section: Discussionmentioning
confidence: 99%
“…Intraperitoneal administration of the newly developed mitochondria-targeted ROS and electron scavenger, XJB-5-131, reversed age-related mitochondrial function alterations and improved contractile properties in skeletal muscle [137]. Oxandrolone improved body composition adaptations to 12 weeks exercise in older women without however increasing muscle function or functional performance beyond that of exercise alone [138]. The benefits of low level laser therapy as an intervention to enhance muscle performance in the elderly is under investigation [139].…”
Section: Perspectives For Futurementioning
confidence: 99%
“…Nandrolone (19-nortestosterone) is an anabolic steroid which through activation of Notch signaling reduces muscle atrophy in sarcopenia rat model [151] . Furthermore, administration oxandrolone in combination with progressive resistance training improved body composition in elderly women [239] . In addition, non-steroidal selective androgen receptor modulators (SARMs) represent therapeutics for the treatment of sarcopenia.…”
Section: Sex Steroid Hormones Therapy For Sarcopeniamentioning
confidence: 97%